PENGARUH MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP HASIL DAN PENGALAMAN BELAJAR PADA MATERI BESARAN DAN PENGUKURAN - Purba, Heri Junawan; Dike, Daniel; Wahyudi, Heri (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to improve students’ learning outcomes and learning experiences through the Children Learning in Science (CLIS) model on the topic of quantities and measurement. The research employed an experimental design with a population consisting of all seventh-grade students divided into two classes: VII-A and VII-B. Class VII-A, consisting of 21 students, was assigned as the experimental group, while class VII-B, consisting of 22 students, served as the control group. The results of the independent samples t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the experimental group using the CLIS model and the control group using conventional teaching methods. The average learning outcome score of the experimental group was 74.86, while the control group scored 66.77. In addition, the test results also revealed a significant difference in students’ learning experiences, with a significance value of 0.000 < 0.05. The average score of learning experience in the experimental group reached 81.61, whereas the control group obtained only 54.11. These findings indicate that the CLIS model is more effective in improving both students’ learning outcomes and learning experiences, creating a more meaningful, active, and enjoyable learning environment.